The web of hate : fragmentation of media authority and its link to right-wing populism and cyber Islamophobia - Aydin, Zeynep; Fuess, Albrecht; Sunier, Thijl; Vázquez, Araceli González (Penerbit Universiti Kebangsaan Malaysia, 2021)
The twenty-first century has been marked strongly with two extremely significant developments, firstly the increase in international terror attacks and secondly the evolution of media and information consumption based on technological advancements. These phenomena together have led to the figurative and literal blowing up of mass media coverage, but, increasingly and more importantly, social media traffic. This shift in information consumption by the general public, especially after terror attacks, is leading to a fragmentation of authority that traditional media gained after years of being the monopoly of verified information exchange. The increased usage and wide accessibility of social media is allowing more people to feel connected globally after terror attacks and is leading to the creation of mediascapes by defining in-groups of like-minded people against Islam, as a common enemy, which leads to a drastic increase in online hate against Islam and Muslims. Digital mediascapes therefore have the ability to unify participants around an “us” that is specifically against the “other” that is labeled as an enemy. Islamophobia thus has become a useful tool for right-wing populists not only to gather a large following online but for right-wing parties to assemble electors in several European nation-states. This, in turn, can provoke the escalation of right-wing populism where people, who are experiencing the echo chamber first hand or those perceiving the viral developments from outside, can become easy prey for political influence. Therefore, social media groups, hashtags and sites can be seen as the feeding ground for right-wing populist political parties.